Combined Longshore and Cross-Shore Modeling for Low-Energy Embayed Sandy Beaches - Yen Hai Tran; Patrick Marchesiello; Rafael Almar; Duc Tuan Ho; Thong Nguyen; Duong Hai Thuan; Eric Barthélemy (Journal of Marine Science and Engineering, 2021)
The present study focuses on the long-term multi-year evolution of the shoreline position of the Nha Trang sandy beach. To this end an empirical model which is a combination of longshore and cross-shore models, is used. The Nha Trang beach morphology is driven by a tropical wave climate dominated by seasonal variations and winter monsoon intra-seasonal pulses. The combined model accounts for seasonal shoreline evolution, which is primarily attributed to cross-shore dynamics but fails to represent accretion that occurs during the height of summer under low energy conditions. The reason is in the single equilibrium Dean number <semantics>Ωeq</semantics> of the ShoreFor model, one of the components of the combined model. This equilibrium Dean number cannot simultaneously account for the evolution of strong intra-seasonal events (i.e., winter monsoon pulses) and the annual recovery mechanisms associated with swash transport. By assigning a constant value to <semantics>Ωeq</semantics>, when the surf similarity parameter is higher than <semantics>3.3</semantics> (occurrence of small surging breakers in summer), we strongly improve the shoreline position prediction. This clearly points to the relevance of a multi-scale approach, although our modified <semantics>Ωeq</semantics> retains the advantage of simplicity.